Prevalence and new histopathological aspects of Haemoproteus spp. in pigeons from Iran - BAHRAMI, S.; ESMAEILZADEH, S.; ALBORZI, A. R.; NIKNEJAD, S. (Journal of the Hellenic Veterinary Medical Society, 2020)
Haemoproteus spp. is pathogenic protozoan that effecting blood circulatory system of birds. The present study was undertaken to evaluate the presence of Haemoproteus spp. in pigeons from Iran and associatedhistopathological changes. A total of 108 blood samples were taken from pigeons to investigate Haemoproteus spp. presence by blood smear and semi-nested PCR targeting the cytochrome b gene methods. Also, to evaluate histopathological changes 12 infected pigeons to Haemoproteus were sacrificed and studied. 34.2% of pigeons infected with Haemoproteus showed macro and microgametocytes in their erythrocytes while based on the molecular method 63.8% were infected. Focal lymphocytic aggregates, pigmentation and cell swelling were the main histopathological lesions in infected livers. Multifocal non- suppurative interstitial nephritis, pigmentation and splenic lymphoid hyperplasia were also seen in the infected pigeons. Mild lymphocytic myocarditis in the heart of one pigeon was the other finding. No histopathological changes were seen in brain, intestine, and pancreas. Schizonts with variable shapes and sizes were detected in infected livers, lungs, kidneys, and spleens but megaloschizonts were not found. This study also reports the molecular prevalence of Haemoproteus spp. in Iran